2020
DOI: 10.1371/journal.pone.0229732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal hepatitis B surface antigen positive status on the pregnancy outcomes: A retrospective study in Xiamen, China, 2011-2018

Abstract: Objective Hepatitis B virus infection is a major social and economic burden in developing countries, especially in China. We aimed to evaluate the effects of hepatitis B surface antigen (HBsAg) positive status on the pregnancy outcomes in the Chinese population. Methods This retrospective cohort study was performed using data from the Medical Birth Registry of Xiamen, China, from January 2011 to March 2018. Multivariate logistic regression analysis was used to assess the association between the HBsAg status an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 26 publications
(35 reference statements)
3
26
1
Order By: Relevance
“…Thirty eligible articles concerning the effect of HBV infection on pregnancy complications were included to assess the effects of HBV on preterm birth 14–17,19–25,27,28,30–38,40–47 . The results revealed significantly higher rates of preterm birth among HBV+ women compared to HBV− women ( p < 0.01) [OR (95% CI) = 1.26 (1.14–1.40)].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty eligible articles concerning the effect of HBV infection on pregnancy complications were included to assess the effects of HBV on preterm birth 14–17,19–25,27,28,30–38,40–47 . The results revealed significantly higher rates of preterm birth among HBV+ women compared to HBV− women ( p < 0.01) [OR (95% CI) = 1.26 (1.14–1.40)].…”
Section: Resultsmentioning
confidence: 99%
“…There is still some controversy about the relationship between HBV infection and PTB in China and worldwide [ 8 10 ]. Jue Liu et al studied 489,965 pregnant women through a national cohort study and found that HBsAg positive patients increase the risk of premature delivery.…”
Section: Discussionmentioning
confidence: 99%
“…1 , 6 Thus, prevention of mother-to-child transmission is an essential step in reducing the global burden of chronic HBV. 5 Although there are inconsistencies, studies have reported that maternal HBV infection is associated with preterm birth, 7 miscarriage, 8 gestational diabetes mellitus, 9 , 10 pregnancy-induced hypertension and preeclampsia. 11 …”
Section: Introductionmentioning
confidence: 99%
“…1,6 Thus, prevention of mother-to-child transmission is an essential step in reducing the global burden of chronic HBV. 5 Although there are inconsistencies, studies have reported that maternal HBV infection is associated with preterm birth, 7 miscarriage, 8 gestational diabetes mellitus, 9,10 pregnancy-induced hypertension and preeclampsia. 11 The prevalence of HBV infection among pregnant women and its associated factors varies across studies [12][13][14][15][16][17] and therefore studies from different settings are crucial to precisely measure the burden of the problem, and to make informed decisions.…”
Section: Introductionmentioning
confidence: 99%